PENGGUNAAN PODCAST UNTUK MEMPERBAIKI PENGUCAPAN (PRONUNCIATION) MAHASISWA DALAM BERBICARA BAHASA INGGRIS (Sebuah Penelitian Tindakan Kelas pada Mahasiswa Pendidikan Bahasa Inggris Semester I Kelas 01, FKIP UNISRI pada Tahun Akademik 2019/2020 ) - Riyani Riyani; Ayu Istiana Sari (Universitas Slamet Riyadi, 2020)
The objective of this research is to know whether Podcast can improve the students’ pronunciation in speaking English when it is implemented in teaching learning process in class 01 Semester I, English Education Program, Teacher Training and Education Faculty, UNISRI, Surakarta in 2019/2020 Academic Year.This research method used a Classroom Action Research which was implemented in two cycles. The subject of the research was class 01 Semester I, English Education Program, Teacher Training and Education Faculty, UNISRI, Surakarta in 2019/2020 Academic Year. This study was conducted in two cycles. The first cycle consisted of four meetings, and the second cycle consisted of three meetings. The procedure of the action research consisted of planning, acting, observing and reflecting. The data were collected through questionnaire, interview, field notes, and test. To analyze the quantitative data, the researcher applied descriptive statistics. It was used to compare the scores and means of pre-test and post-test. The pre-test was conducted in the preliminary research while post-test was conducted at the end of cycle 1 and 2. The result of the test was used to know how well the students understand the text of listening. To analyze the qualitative data, the researcher analyzed the improvement of the teaching learning process based on the results of questionnaire, interview, and field notes.The result of the research showed that the use of Podcast has helped students to get exposed to correct pronunciation. By constantly listening to Podcast of native speakers of English, students develop their skill not only in listening but also in pronouncing the words in English correctly. It also has helped the students in improving the students’ vocabulary mastery. In conclusion, by listening to Podcast, students can improve their pronunciation and vocabulary mastery so that they also can speak more during the speaking activity.Based on the result of the study, it can be concluded that students’ pronunciation in English can be improved by the use of Podcast. Therefore, it is recommended that teachers and students can use Podcast as one of the alternative techniques in teaching and learning speaking.Keywords : Podcast, Proununciation, Speaking Skill, Action Research